Current Developments and Perspectives on the Diagnosis and Treatment of Urinary Incontinence and Genital Prolapse in Women - Naumann, G.; Kölbl, H. (Geburtshilfe und Frauenheilkunde, 2012)
As a key area of gynaecology, urogynaecology has undergone impressive changes in the past few years. Together with the high prevalence of functional pelvic floor disorders, modern anaesthesia procedures and the introduction of new, innovative minimally invasive operation techniques have led to a dramatic increase in the number of operations for incontinence and prolapses. The increasingly subtle diagnostic options, such as, e. g., 2D and 3D sonography of the pelvic floor provide unambiguous findings and facilitate decision making. Tension-free vaginal slings in retro-pubic, trans-obturator or single-incision techniques show a high success rate with few complications and have almost completely replaced the more invasive abdominal surgical techniques for the operative management of stress incontinence. Especially for recurrent prolapse the use of alloplastic nets leads to a markedly improved anatomic and functional outcome. In spite of the euphoria about modern operation techniques and novel net materials, in-depth knowledge of pelvic floor anatomy, sufficient surgical experience and unequivocal guideline-conform indications are mandatory for satisfactory treatment outcomes. The afflicted women must be informed in detail about alternative procedures and more emphasis should be placed on conservative therapy. Novel surgical techniques should be monitored by registers or clinical trials. The professional society is called upon to improve the training curricula for pelvic floor surgery.
Keywords: urogynecology; aconuresis; descensus